Issues and challenges in financing the poor: case of Baitul Maal Wa Tamwil in Indonesia - Wulandari, Permata; Kassim, Salina (Emerald Publisher, 2016)
The purpose of this paper is to highlight the issues and challenges in providing financing to the poor people based on the experience of Baitul Maal Wa Tamwil (BMT) in Indonesia. A series of structured interviews were conducted with the chairman and staff of the Central BMT (Induk Koperasi Syariah) in Jakarta which is the head-quarter of 382 BMTs throughout Indonesia, with additional chairman and shari’ah supervisory in Central BMT (Pusat Koperasi Syariah) in Makasar. Subsequently, the results from the structured interviews were analyzed using qualitative analysis to arrive at the model of the peculiarities of financing the poor in Indonesia. The findings show that the Central BMT has built specific products and empowerment mechanisms for the poor and has an ideal product to be applied in 382 BMT in Indonesia. There are two schemes of financing source in BMT, namely, social ministry (Kelompok Usaha Bersama) and private financing (national and international donor). Specifically, the peculiarities of financing given in BMT are not only in the term of capital but also in the term of providing infrastructure and training for the poor. Moreover,collateral must be provided as a screening process for the poor people to secure any form of financing. If there is no collateral, potential borrowers must opt for joint-liability financing. Furthermore, if the poor could not repay the financing, endowment coming from charity and compulsory Islamic tax (zakat, infaq and sadaqah) would play a vital role to cover for the financing default. Lastly, religious capacity building is also provided as a part of risk management aspect.